Evaluating seabed habitat representativeness across a diverse set of marine protected areas on the Mid-Atlantic Ridge - Milla-Figueras, David (2021)
Marine ecosystem-based management requires good spatial information on the distribution of marine species and habitats. Often, such information is limited to a few sampled locations, but modelling techniques can be applied to produce predictive distribution maps. A harmonized broad-scale seabed habitat map was recently produced for the archipelagos of Macaronesia under the EMODnet Seabed Habitats Programme. We use this new information to produce an extent-based evaluation of the representativeness and level of protection conferred by the current set of marine protected areas (MPAs) in the Azores to the variety of benthic marine habitats found in this oceanic region. A more objective assessment of the protection effectively provided to the habitats is obtained by applying a scoring system to the MPAs based on the number of allowed extractive and non-extractive human activities and their potential impact on marine biodiversity and habitats. Results show that Azorean habitats within the MPAs are nearly entirely classified as highly protected. In total, 26 habitats (7 of which are endangered and 2 are rare) have at least 10% of their extent in the Azores EEZ protected by MPAs, but another 29 fail to meet this target (4 on-shelf habitats and 25 deep-sea habitats), highlighting the need to extend current protection of bathyal and abyssal habitats and applying adequate ecological coherence criteria. This approach sets a standard that can be used wherever similar information is available, be it in other European regions or beyond.